How Good Is our Place—Implementation of the Place Standard Tool in North Macedonia - Dragan Gjorgjev (International Journal of Environmental Research and Public Health, 2019)
This study describes the implementation, in North Macedonia, of a “tool”, initially devised in Scotland, to generate community and stakeholder discussion about the places in which they live and notably a place’s capacity to generate health wellbeing and greater equity among citizens. In this study, the “place standard tool” (PST) is viewed from the perspective of creating places which can deliver a triple win of health and wellbeing, equity, and environmental sustainability. Skopje, North Macedonia’s capital, inevitably differs economically, culturally, and politically from Scotland, thus providing an opportunity to augment existing knowledge on adaptability of the tool in shaping agendas for policy and action. Тhe PST was tested through seminars with selected focus groups and an online questionnaire. Over 350 respondents were included. Information on priorities enabled the distillation of suggestions for improvement and was shared with the Mayor and municipal administration. Skopje citizens valued an approach which solicited their views in a meaningful way. Specific concerns were expressed relating to heavy traffic and related air and noise pollution, and care and maintenance of places and care services. Responses varied by geographic location. Application of the PST increased knowledge and confidence levels among citizens and enthusiasm for active involvement in decision making. Effective implementation relies heavily on: good governance and top-level support; excellent organization and good timing; careful training of interviewers and focus group moderators; and on prior knowledge of the participants/respondents.